Domestic and international trade liberalisation of the indian economy: domestic firms & MNCs response - Khan, Tahsan Rahman; Bashir, Md. Mamoon Al; Choudhury, Tonmoy Toufic; Adnan, Ashique Mahmood (International Affairs and Global Strategy, 2016)
This article was published in International Affairs and Global Strategy [© 2014 International Affairs and Global Strategy] and the definite version is available at : http://iiste.org/Journals/index.php/IAGS/article/view/12237/12590 The article website is at: http://iiste.org/Journals/index.php/IAGS The journal is licensed under a Creative Commons Attribution 3.0 Unported (CC BY 3.0) License.